2009
DOI: 10.1111/j.1365-2516.2009.02051.x
|View full text |Cite
|
Sign up to set email alerts
|

Age‐dependent increase of FVIII:C in mild haemophilia A

Abstract: Variability of FVIII:C levels in healthy individuals and age-dependent increase are a known phenomenon. In haemophilia, increasing FVIII:C levels with age have not been described yet. In our study, we evaluated this issue retrospectively in a cohort older than 45 years of 29 patients with mild haemophilia and 14 patients with moderate or severe haemophilia at last visit at the haemophilia centre Frankfurt. The median duration of observation evaluated in this study was 17 years (range 5-28). Results show a sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
16
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 18 publications
1
16
0
1
Order By: Relevance
“…Seary et al [9] found, in their study of 74 boys with 38 different mutations causing moderate or mild hemophilia, that age and FVIII level were strong predictors of response to desmopressin. The stronger effect of desmopressin in older patients in our study may reflect the increase in baseline FVIII levels with age, as previously described by Miesbach et al [10], but our model does not completely explain the variation in the effect of DDAVP. Larger groups of patients are needed to better evaluate the effects of VWF:Ag, blood group and age on baseline FVIII levels and in relation to test results.…”
supporting
confidence: 51%
See 1 more Smart Citation
“…Seary et al [9] found, in their study of 74 boys with 38 different mutations causing moderate or mild hemophilia, that age and FVIII level were strong predictors of response to desmopressin. The stronger effect of desmopressin in older patients in our study may reflect the increase in baseline FVIII levels with age, as previously described by Miesbach et al [10], but our model does not completely explain the variation in the effect of DDAVP. Larger groups of patients are needed to better evaluate the effects of VWF:Ag, blood group and age on baseline FVIII levels and in relation to test results.…”
supporting
confidence: 51%
“…While both the plasma-and platelet-derived molecules can form a functional complex, several studies demonstrate that the two cofactor pools are physically and functionally distinct [2][3][4][5][6][7]. Despite these differences, the entire platelet-derived pool of the procofactor, FV, is endocytosed from the plasma by megakaryocytes [4,8] via a two-receptor system consisting of a specific, unknown FV receptor and low density lipoprotein (LDL) receptor-related protein-1 (LRP-1) [9], an endocytic receptor belonging to a superfamily of proteins related to the LDL receptor [10]. Flow cytometric analyses and fluorescence microscopy indicate that all megakaryocytes express LRP-1 [9,11].…”
mentioning
confidence: 99%
“…In hemophilia A, FVIII levels increase with age, particularly in mild disease. (14) The clinical significance of this change has not been determined. In one retrospective cohort study, the authors describe increased bleeding in HA patients with increased age.…”
Section: Introductionmentioning
confidence: 99%
“…Underlying predispositions of the carriers like type of mutation or severity of haemophilia A in the male relatives might have an influence on bleeding tendency. Contributing factors to FVIII:C levels might be age and comorbidities [5] or type of blood group [6]. Notably, the wide range of FVIII:C levels found in carriers does not always show a clear correlation between bleeding tendency and factor level in carriers, which might in part be explained by other factors as thrombophilic genotypes.…”
Section: Introductionmentioning
confidence: 99%